Citrulluslanatus: An Overview on Pharmacological Activities - Kumawat, G (International Journal of Pharmaceutical & Biological Archive, 2017)
The Citrulluslanatus is commonly known as Water melon. Citrulluslanatus is an important ethanomedicinal plant grows in India, Africa, Asia and USA. Various parts of the Citrulluslanatus such as fruit pulp, juice, rind, seeds and leaves are used as ethanomedicine. The pharmacological studies conducted onCitrulluslanatus depicted antimicrobial, antigiardial, hepatoprotective, anti-ulcer genic property, anti-diabetic, laxative, antisecretory effects, anti-prostatic hyperplasia, antioxidant, analgesic, antifungal, anti-inflammatory effects in animal models. The present review is an effort to compile information regarding botanical descriptionand pharmacological activities of Citrulluslanatusto stimulate further scientific research.